Cyclization of Multi Components Reactions and (Preparation, Investigation, Thermal Curves) - Aljamali, Nagham Mahmood; Abd Allattif, Nour Abd Alrazzak; Abdalrahman, Sabreen Ali (American International Journal of Multidisciplinary Scientific Research, 2018)
Many cyclic compounds were formatted via multi components reactions and cyclization reaction through many steps with ( various conditions , various starting materials , various components ), in first step , aromatic amine derivative were reacted with ammonium thiocyanate in cyclization reaction to yield 2-aminobenzothiazole derivative , which reacted with formaldehyde and benzaldehyde as a multi components reaction ., then the resulting compounds cyclized with ( semicarbazide , ortho-phenyl diamine , ortho-thiol aniline , ortho- amino phenol ). Investigation of compounds carried out through many techniques ( FT.IR , H.NMR , Mass ) – Spectra , Thermal studies